Estudo de vocábulos para avaliação de crianças com deficiência sem linguagem oral - Paura, Andréa Carla [UNESP]; Deliberato, Débora [UNESP] (Associação Brasileira de Pesquisadores em Educação Especial - ABPEE, 2014)
Researchers in the field of Augmentative and Alternative Communication point out the lack of instruments for assessing children and young people with a complex communication needs. This study's focus is the selection of words for creating an instrument for the vocabulary range in non-speaking children aged two to eleven years and eleven months. Three studies were performed. The first study identified and described tools available for assessing receptive vocabulary and their respective word lists. The second identified and described research that presented word inventories or word lists. The third study identified the vocabulary reported by parents and teachers. The words that were identified in the three studies were analyzed according to: the number of times they occurred; the Picture Communication Symbols system classification; and a semantic and syntactic classification. Based on these studies the following criteria for vocabulary selection were established for word selection: the 45 words which appeared in all three studies, the words that occurred five times or more, considering the three studies, representing 167 (14.14%) words; the words identified in study one or two, but that had been reported by the families - 183 (19.37% out of 945 words) - or by teachers - 108 (11.43% out of 945 words). The word list was composed of 269 items, classified in 18 semantic and syntactic topics; it represents an initial tool for professionals in the field of health and education to set goals for beginning assessment of children and teenagers who are users of Augmentative and Alternative Communication systems.

Pesquisadores da área de comunicação suplementar e alternativa consideram a falta de instrumentos para avaliar crianças e jovens com necessidade complexa de comunicação. Este trabalho objetivou selecionar vocábulos para um instrumento de avaliação do repertório de vocabulário de crianças não-oralizadas com idade de dois a 11 anos e 11 meses. Para a seleção dos vocábulos foram realizados três estudos. O primeiro estudo identificou e descreveu instrumentos disponíveis para avaliação do vocabulário receptivo e suas listas de vocábulos. O segundo estudo identificou e descreveu pesquisas que apresentaram inventários ou listas de vocábulos empregados por crianças e seus parceiros de comunicação. O terceiro estudo identificou o vocabulário relatado por pais e professores. Os vocábulos identificados nos três estudos foram analisados de acordo com: o número de ocorrência dos vocábulos; a classificação do sistema Picture Communication Symbols e uma classificação semântica e sintática. A partir dos estudos foram estabelecidos como critérios para a seleção dos vocábulos: os 45 vocábulos presentes nos três estudos; os vocábulos que tiveram ocorrência maior ou igual a cinco, considerando os três estudos, representando 167 (14,14%) vocábulos; os vocábulos que estiveram presentes no estudo 1 ou 2, mas que foram citados pelas famílias, 183 (19,37% de 945 vocábulos) ou pelas professoras 108 (11,43% de 945 vocábulos). A lista de vocábulos apresentou 269 itens, classificadas em 18 temas semânticos e sintático e representa um instrumento inicial para profissionais da saúde e educação estabelecerem metas para a avaliação inicial de crianças e jovens usuários de sistemas de comunicação suplementar e alternativa.
Study of words for assessing non-speaking children with disabilities
Keywords: Educação Especial; Sistemas de Comunicação Alternativos e Suplementares; Paralisia Cerebral; Vocabulário; Linguagem Infantil; Special Education; Augmentative and Alternative Communication; Cerebral Palsy; Vocabulary; Child Language